Pengembangan Sistem Pendukung Keputusan Pemilihan Siswa Berprestasi Berbasis Multi-Kriteria Menggunakan Metode Simple Additive Weighting (SAW) pada Sekolah Menengah Kejuruan - Samsir; Maisarah Ritonga; Muhammad Siddik (CSRID (Computer Science Research and Its Development Journal), 2026)
The selection process of outstanding students in Vocational High Schools (SMK) often suffers from subjectivity and inefficiency due to manual assessment procedures. This study aims to develop a web-based Decision Support System (DSS) using the Simple Additive Weighting (SAW) method to determine outstanding students more objectively. The system integrates three achievement categories—academic, professional, and sports achievements—represented by nine evaluation indicators with different weights according to their importance. The SAW method was applied through decision matrix construction, normalization, weighting, and preference value calculation. The results show that the best alternative obtained a preference value of 6.77 and was recommended as the outstanding student. Black Box testing indicated that all system functions operated successfully with a 100% success rate. Furthermore, the system reduced the selection process time from 40 minutes to 8 minutes, representing an 80% efficiency improvement compared with the manual process. These findings demonstrate that the implementation of the SAW method effectively improves objectivity, transparency, and efficiency in the outstanding student selection process in vocational high schools.